2015
DOI: 10.1016/j.canlet.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Oxovanadium-based inhibitors can drive redox-sensitive cytotoxicity in neuroblastoma cells and synergise strongly with buthionine sulfoximine

Abstract: In a wide range of neuroblastoma-derived lines oxovanadium compounds such as bis(maltolato)oxovanadium(IV) (BMOV) are cytotoxic. This is not explained by oxidative stress or inhibition of ion channels. Genotoxicity is unlikely given that a p53 response is absent and p53-mutant lines are also sensitive. Cytotoxicity is inhibited by N-acetyl cysteine and glutathione ester, indicating that BMOV action is sensitive to cytoplasmic redox and thiol status. Significantly, combining BMOV with glutathione synthesis inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 75 publications
5
28
0
Order By: Relevance
“…Inorganic V salts, e.g., Na 3 VO 4 or VOSO 4 ⋅5 H 2 O, and anti‐diabetic V IV complexes, e.g., 1 , undergo complex speciation in biological media, as discussed earlier in the review, but the products of this speciation are often assumed to be relatively non‐toxic, although they were highly cytotoxic in some cell lines (Table S1) . Both Na 3 VO 4 and 1 converge within 24 h at 310 K into the same mixture of decomposition products (≈75 % V V and ≈25 % V IV complexes with protein and carbohydrate ligands), which were probably mostly responsible for the observed biological activity.…”
Section: Cytotoxicity Mechanisms Of Vanadium Complexes and Implicatiomentioning
confidence: 99%
See 4 more Smart Citations
“…Inorganic V salts, e.g., Na 3 VO 4 or VOSO 4 ⋅5 H 2 O, and anti‐diabetic V IV complexes, e.g., 1 , undergo complex speciation in biological media, as discussed earlier in the review, but the products of this speciation are often assumed to be relatively non‐toxic, although they were highly cytotoxic in some cell lines (Table S1) . Both Na 3 VO 4 and 1 converge within 24 h at 310 K into the same mixture of decomposition products (≈75 % V V and ≈25 % V IV complexes with protein and carbohydrate ligands), which were probably mostly responsible for the observed biological activity.…”
Section: Cytotoxicity Mechanisms Of Vanadium Complexes and Implicatiomentioning
confidence: 99%
“…Anti‐cancer activity studies of 1 (or more likely of its reaction products with cell culture media) in human neuroblastoma cells showed that V cytotoxicity varies by at least an order of magnitude, even in closely related cell lines. In agreement with data from V V salts (Section 2.1), the cytotoxicity of 1 strongly correlated with cellular thiol levels …”
Section: Reactivity and Anti‐proliferative Activity Of Vanadium Complmentioning
confidence: 99%
See 3 more Smart Citations